Morphological responses of Andean blueberry (Vaccinium meridionale Swartz) plants growing in three environments at different altitudes - Becerra, Andrés David; Quevedo-Rubiano, Santiago; Magnitskiy, Stanislav; Lancheros, Héctor Orlando (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
The Andean blueberry (Vaccinium meridionale Swartz) is a promising fruit crop that has gained importance in the market because of its nutritional and medicinal properties; however, there are few studies on the optimal conditions for growth and production. In this study, the vegetative growth of Andean blueberry plants was evaluated for 200 days in three sites at different altitudes in the Department of Cundinamarca (Colombia): municipality of San Francisco (1,885 m a.s.l.), Bogota (Universidad Nacional de Colombia - UNAL, 2,556 m a.s.l.), and Cruz Verde páramo (3,298 m a.s.l.). For the evaluation, 2-year-old plants were used that were propagated in vitro. The experiment had a repeated measures design, with 3 treatments (locations) and 5 data collection times, with destructive measurements at the beginning and at the end of the trial. Data for leaf area per plant, plant height, stem width, number of primary branches, branch length, and chlorophyll contents in leaves were taken. The tallest plants, with the largest leaf area and most dry matter, were found at the UNAL (2,556 m a.s.l.). Morphological and physiological variations were observed in response to each of the environments, with correlations between the growth variables and the environmental variables. The highest percentage distribution of dry matter in leaves was in the plants from the Cruz Verde páramo (3,298 m a.s.l.), while the percentage distribution of dry weight in the stem was higher in the plants from San Francisco (1,885 m a.s.l.). The percentage distribution of root dry weight was greater in the plants from San Francisco than those from other locations. The results indicated that the Andean blueberry plants had the most suitable conditions for vegetative growth at altitudes close to 2,556 m a.s.l.